Current status of hematopoietic stem cell transplant in chronic myeloid leukemia - Alok Gupta; Navin Khattry (Indian Journal of Medical and Paediatric Oncology)
Indications for hematopoietic stem cell transplant (HSCT) in chronic myeloid leukemia (CML) have changed over time. This change has largely been influenced by the advent of tyrosine kinase inhibitors, increased understanding of the mechanisms underlying disease phase progression as well as drug resistance, refinement of transplant techniques and exploitation of graft versus leukemia effect in this disease. Here, we have discussed the status of HSCT in CML in the present era with regards to the current indications, factors determining outcome and management strategies for posttransplant relapse.